Communication Outreach on Gadget Usage Education for Elementary School Children - Adinda Nur Azizah Rakhma; Dwi Nurul Desilawati; Dara Khoeru Nisa; Umi Kalsum (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
Every time there is a change in life, there are always updates in life, one of which is technology such as gadgets, electronic devices which have many advantages, starting from the function and benefits of gadgets which can make things easier and don't take up much time when used and taken anywhere. Gadgets are electronic devices that function for communication, tools for productivity, entertainment, and as tools to help certain activities. However, some people cannot use gadgets according to their function, therefore in the communication outreach regarding education on the use of gadgets for elementary school children, directions are given so that they can use gadgets according to their functional portion. From this counseling, the results of this activity can increase parents' knowledge regarding monitoring gadget use.